Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Tropical or extratropical cyclones: what drives the compound flood hazard, impact, and risk for the United States Southeast Atlantic coast? - Kees Nederhoff; Tim W. B. Leijnse; Kai Parker; Jennifer Thomas; Andrea O’Neill; Maarten van Ormondt; Robert McCall; Li Erikson; Patrick L. Barnard; Amy Foxgrover; Wouter Klessens; Norberto C. Nadal-Caraballo; et al. (Natural Hazards, 2024)
Subtropical coastlines are impacted by both tropical and extratropical cyclones. While both may lead to substantial damage to coastal communities, it is difficult to determine the contribution of tropical cyclones to coastal flooding relative to that of extratropical cyclones. We conduct a large-scale flood hazard and impact assessment across the subtropical Southeast Atlantic Coast of the United States, from Virginia to Florida, including different flood hazards. The physics-based hydrodynamic modeling skillfully reproduces coastal water levels based on a comprehensive validation of tides, almost two hundred historical storms, and an in-depth hindcast of Hurricane Florence. We show that yearly flood impacts are two times as likely to be driven by extratropical than tropical cyclones. On the other hand, tropical cyclones are 30 times more likely to affect people during rarer 100-year events than extratropical cyclones and contribute to more than half of the regional flood risk. With increasing sea levels, more areas will be flooded, regardless of whether flooding is driven by tropical or extratropical cyclones. Most of the absolute flood risk is contained in the greater Miami metropolitan area. However, several less populous counties have the highest relative risks. The results of this study provide critical information for understanding the source and frequency of compound flooding across the Southeast Atlantic Coast of the United States.